Cervical Medial Branch Blocks For The Diagnosis Of Somatosensory Tinnitus. A Pilot Study. - Klessinger Stephan (Journal of Otolaryngology Advances, 2016)
The purpose was to discover if medial branch blocks (MBBs) of the cervical spine can be used as a diagnostic tool to identify patients with somatosensory tinnitus. MBBs are a diagnostic tool to confirm the diagnosis facet joint pain in patients with neck pain. It is not known, if MBBs are also suitable for testing other symptoms than pain. However, the existence of neural connections between the auditory system and the cervical region can be assumed. Included were 22 consecutive patients presenting with tinnitus, who had received MBBs in a ten years’ period. Patients were tested with a MBB with bupivacaine and triamcinolone. Injections were performed with fluoroscopic visualization using established techniques. The mean follow-up time was 6.2 weeks. Tinnitus was analyzed through the global clinical impression of the patient. Seven patients (31.8 %) experienced a significant improvement of the tinnitus. In one patient a thermal radiofrequency neurotomy was done after positive response to two MBBs. The pain relief and a significant reduction of the tinnitus sustained at the follow-up examination 20 weeks after the denervation. No statistically significant difference was found in age, gender, duration of symptoms, additional neck pain or vertigo, or side or level of the intervention. This pilot study shows the feasibility to identify patients with somatosensory tinnitus with MBBs. Further studies with the primary intention on tinnitus are necessary to prove the significance of MBBs. After a positive response to MBBs, treatment with radiofrequency neurotomy is the rational consequence.
Keywords: Somatosensory Tinnitus